Amino acid composition of food products used in the treatment of patients with disorders of the amino acid and protein metabolism - Bremer, Hans J.; Anninos, Alexandros; Schulz, B. (European journal of pediatrics, 1996)
The amino acid composition of food products frequently used in the diets of amino acid and protein disorders — including tryptophan — was estimated using ion-exchange column chromatography and high performance liquid chromatography. It includes fruits (different varieties of apples, pears, ananas, bananas, peach, strawberries, honey melon, water melon, kiwi, plums, grapes), vegetables (different varieties of potatoes, potato products, cauliflower, broccoli, cabbages, spinach, olives, lettuce, cucumber, peas, mushrooms) and commercially available or home-made food products (meat broth, fine gravy paste, ketchup, liquid seasoning, soja sauce, different varieties of Chinese noodles, sausages for phenylketonuria patients), and different new fiber concentrates.